Water current measurements using oceanographic bottom lander LoTUS. (January 2020) - Kjelldorff, Maria; Kuttenkeuler, Jakob; Kirchner, Nina; Krützfeldt, Jari; Sundberg, Mikael
Highlights: Suitable Eulerian method for long term ocean current velocity measurements Robust, low cost and practical bottom lander for ocean current velocity observation. Experiments verifying modeling and hydrodynamics of the sensing system. Abstract: LoTUS is a bottom landing, Lo ng T erm U nderwater S ensing node made for the observation of ocean water temperatures. LoTUS is moored to the seafloor and measures temperature according to a specified time schedule until, at the end of the mission, it surfaces to transmit the collected data to on-shore recipients using an Iridium link. The paper presents an extension of the sensing capability which includes water current velocity (speed and direction) using a robust, reliable and inexpensive Eulerian method. The method is based on the "tilting stick" principle where a combination of inertial and magnetic measurement data are used. The paper discusses the principal technique, modeling of the system, practical considerations, optimization of the setup for specific flow conditions, and the verification of experimental data.